A NEW HYBRID MODEL TO EVALUATE THE LOSS OF LIFE OF POWER TRANSFORMERS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
Following the thermal model for assessing the degradation of transformer units, as advocated by IEEE and IEC standards, existing literature posits that the transformers do not exhibit significant aging at hot-spot temperatures below 90°C. Contrary to this prevailing understanding, the current study demonstrates that when using a model based on insulation resistance measurements, discernible aging of transformers occurs even at these lower hot-spot temperature thresholds. Consequently, this paper introduces a novel evaluative hybrid model for transformer degradation, designed to be applicable across the entire range of hot-spot operational temperatures.
Keywords: Loss of life; Aging; Transformers; Thermal model; Insulation resistance model